FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAKTU VISITE DOKTER - Chairissy, Marsha Dechastra (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Factors Influencing Ward Rounds Time Compliance Patient satisfaction is the goal of improving the quality of health services. Indonesia Minister of Health Regulation Nomor. 30 of 2022 has set national quality indicator targets, one of which is ward rounds time compliance. Qualitative case study was performed to explore what factors influence ward rounds time compliance at hospitals. Data was collected through focus group discussions and semi-structured interviews. Secondary data also used to support this study. From the research results, it was found that man, method, machine, and environment factors play a role in non-compliance with doctor visit times. Lack of knowledge regarding applicable laws and regulations, hospital regulations that are not binding on doctors, lack of commitment from doctors, no follow-up on compliance reports during ward rounds, no reward and punishment system and also hospital culture are factors that play a role in low compliance rate during hospital ward rounds.